2016
DOI: 10.3390/toxins8100301
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fusarium Toxin Accumulation in Grain of Winter Triticale Lines Inoculated with Fusarium culmorum as Compared with Wheat

Abstract: Resistance to Fusarium head blight in 32 winter triticale and 34 winter wheat accessions was evaluated. Triticale and wheat were sown in field experiments in two locations. At the time of flowering, heads were inoculated with three Fusarium culmorum isolates. Fusarium head blight index was scored and after the harvest percentage of Fusarium damaged kernels was assessed. Grain was analysed for type B trichothecenes (deoxynivalenol and derivatives, nivalenol) and zearalenone (ZEN) content. The average Fusarium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…As such, there would seem to be the possibility for greater ramification within the kernel. A recent report by Góral et al [ 45 ] showed higher content of type B trichothecenes in winter triticale than winter wheat varieties grown in inoculated nurseries ( F. culmorum ) at two locations, despite lower FHB disease symptoms occurring in triticale. Triticale is a hybrid of wheat ( Triticum ) and rye ( Secale ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there would seem to be the possibility for greater ramification within the kernel. A recent report by Góral et al [ 45 ] showed higher content of type B trichothecenes in winter triticale than winter wheat varieties grown in inoculated nurseries ( F. culmorum ) at two locations, despite lower FHB disease symptoms occurring in triticale. Triticale is a hybrid of wheat ( Triticum ) and rye ( Secale ).…”
Section: Discussionmentioning
confidence: 99%
“…): KF 846 (DON chemotype), KF 350 (NIV chemotype) and ZFR 112 (ZEN type) ( Góral et al, 2019 ). Equal volumes of conidial suspensions of these three isolates were mixed ( Góral et al, 2016 ). The flowering rye heads (65 ZGS) were inoculated by spraying with the spore suspension at a rate of approximately 100 ml/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The type B trichothecenes (DON, 3-acetyldeoxynivalenol (3AcDON), 15acetyldeoxynivalenol (15AcDON) and NIV) were detected. The methodology used for the extraction and detection of the samples with use of gas chromatography is described in detail by Góral et al [27,36].…”
Section: Toxins Analysismentioning
confidence: 99%
“…The content of ZEN was determined using a quantitative direct, competitive enzyme-linked immunosorbent assay (ELISA) AgraQuant® ZON 40/1000 (LOD 10 ppb) (Romer Labs Inc., Newark, DE, USA). The detailed methodology used for the quantitative analysis of ZEN is described by Góral et al [27].…”
Section: Toxins Analysismentioning
confidence: 99%
See 1 more Smart Citation